Direct observation of a 91 bp LacI‐mediated, negatively supercoiled DNA loop by atomic force microscope. Issue 5 (26th February 2016) - Fulcrand, Geraldine; Chapagain, Prem; Dunlap, David; Leng, Fenfei
Abstract : Escherichia coli lactose repressor (LacI), a tetrameric protein, is a paradigmatic transcriptional factor that controls the expression of lacZYA in the lac operon. It specifically binds to the O1, O2, and O3 operators of the lac promoter, forms DNA loops, and regulates transcription of the lac operon. In this article, utilizing combined techniques of DNA‐nicking assay and AFM imaging, we directly observed a 91 bp LacI‐mediated, negatively supercoiled DNA loop mimicking the DNA loop between the O1 and O3 operators in the lac promoter. Abstract :